Microbial functional structure of Montastraea faveolata , an important Caribbean reef‐building coral, differs between healthy and yellow‐band diseased colonies - Nikole E. Kimes; Joy D. Van Nostrand; Ernesto Weil; Jizhong Zhou; Pamela J. Morris (Environmental Microbiology, 2010)
Summary A functional gene array (FGA), GeoChip 2.0, was used to assess the biogeochemical cycling potential of microbial communities associated with healthy and Caribbean yellow band diseased (YBD) Montastraea faveolata . Over 6700 genes were detected, providing evidence that the coral microbiome contains a diverse community of archaea, bacteria and fungi capable of fulfilling numerous functional niches. These included carbon, nitrogen and sulfur cycling, metal homeostasis and resistance, and xenobiotic contaminant degradation. A significant difference in functional structure was found between healthy and YBD M. faveolata colonies and those differences were specific to the physical niche examined. In the surface mucopolysaccharide layer (SML), only two of 31 functional categories investigated, cellulose degradation and nitrification, revealed significant differences, implying a very specific change in microbial functional potential. Coral tissue slurry, on the other hand, revealed significant changes in 10 of the 31 categories, suggesting a more generalized shift in functional potential involving various aspects of nutrient cycling, metal transformations and contaminant degradation. This study is the first broad screening of functional genes in coral‐associated microbial communities and provides insights regarding their biogeochemical cycling capacity in healthy and diseased states.